Miniaturized Microstrip Ring Hybrid with Defected Microstrip Structure. Issue 10 (26th July 2013) - Salari, Mohammad Ali; Manoochehri, Omid; Abbasiniazare, Seyyedpayam
ABSTRACT A method for miniaturization of microstrip rat‐race hybrid with the aid of "defected microstrip structure (DMS)" is proposed. Each transmission line section is loaded with cascaded DMS sections. This results in slow‐wave characteristics which in turn increases the electrical length of the line. In the frequency range below the bandgap, the phase of S21 is negative and DMS behaves as a slow wave device; allowing a miniaturized structure. A reduction of 50% in the occupied area of the circuit and no bandwidth reduction is achieved using this technique. The miniaturized rat‐race operates at 3.4 GHz and can be used in LTE systems. The circuits are fabricated and the measured and simulated results are in excellent agreement. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2245–2248, 2013